A brief history of Iraq - Fattah, Hala Mundhir, 1950- (Facts on file, 2009)
From the Publisher: The story of Iraq is that of a people struggling to overcome the burdens of a turbulent past. From the ancient Mesopotamian civilizations to the 2003 U.S. invasion and subsequent fall of Saddam Hussein, A Brief History of Iraq takes a concise but comprehensive look at the peoples and cultures of Iraq and the regional influences that shaped the destiny of the country's many ethnicities, religions, sects, and national groups. Because of Iraq's porous frontiers, its accommodating soil and climate, and its diverse inhabitants, its history has been one of interaction, adaptation, acculturation, and modification. These factors have played a major role in the development of the modern nation and provide the context needed to understand the current conflict and efforts to build a stable society and government.